Country Partnership Framework for the Republic of Congo for the Period FY20-FY24 - World Bank Group (World Bank, Washington, DC, 2019)
The Republic of Congo, which joined the ranks of lower middle-income countries on the back of strong oil revenues for more than a decade, has yet to fully leverage its natural resource endowments to achieve robust and sustainable development outcomes. Congo is now resource-constrained at a time when it needs to respond to demands from a growing, increasingly youthful population. Despite its abundant natural resources, Congo remains a fragile and conflict-affected country. This CPF will be organized around two Focus Areas: (i) Strengthening Economic Management to Create an Improved Investment Climate for Private Sector-Led Growth; and (ii) Building Human Capital and Enhancing Resilience for Social Inclusion and Sustainable Growth.